As representações de alunos de um curso superior de Turismo e Hotelaria acerca da disciplina Inglês Instrumental - Lopes, Cleusa Leite (2014)
Undergraduate students start the ESP course at university with representations that influence the process of language learning. A more consistent analysis of those representations and their possible changes has motivated this research. This study aimed to investigate the transformations that occurred with the representations of students of a Tourism and Hotel Undergraduate Program. The research was carried out by comparing the previous representations of English language and initial and final representations in order to find out which of them reflected some of the notions of the Language for Specific Purposes approach. This study is grounded on the concepts of Social Representation discussed by Moscovici (2000/2011), Jodelet (1989/2001); language of emotions, by Ekman (2011); Languages for Specific Purposes (LSP) approach, of which English for Specific Purposes makes part, discussed by Hutchinson and Waters (1987-1996), Dudley-Evans and St. John (1998) and on The Brazilian ESP Project, by Celani, Holmes, Scott and Ramos (1988), Celani et al. (2005) and Ramos (2005, 2008) and on a brief view of new directions for Specific Purposes research (BELCHER et al., 2011). It is a case study (Stake, 1995) and was developed at a private higher education institution, located in the state of São Paulo, Brazil. The participants were thirteen students enrolled in the Tourism and Hotel Undergraduate Program. The data were collected using one questionnaire at the beginning and one questionnaire at the end of the discipline, one report at the beginning and one report at the end of the discipline, and also by interviewing the students at the end of the discipline. The results showed that there were expressive changes in the students' representations and that the Language for Specific Purposes approach is related to these changes. This research indicates the importance of the teacher s awareness regarding his/her students representations. This comprehension may contribute better classroom management, considering the importance of individuals representations within a social group, in a specific context in which the learning process takes place. It may also provide the student with the possibility of participating in a new experience and, based on that experience, change a situation or a felling that disturbs him/her. I consider these concerns relevant for development process of higher education students as professionals